Ratiodecidendi of Judge in Imposing Warning Punishment Against Children in Conflict with the Law from the Perspective of Child Protection - Rakhmatika, Devi; Sami’an, Sami’an (Rechtsnormen: Journal of Law, 2024)
Background. Cases of violence against children still occur frequently in Indonesia. The weak social control of society and the many cases of abuse show that law enforcement in Indonesia is not yet optimal. Purpose. Child Protection has been regulated in Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection. And regulations regarding the Juvenile Justice System are regulated in Law Number 11 of 2012 concerning the Juvenile Justice System, but these regulations are not sufficient to guarantee the cessation of cases of maltreatment against children. Method. The author uses normative juridical research methods. In this case, the Ratio Decidendi of the Judge does not really see from various points of view, it can be seen from the consideration that in the end the Judge imposed a warning sentence on the Child Convict, and the decision did not explain and pay attention to the rights of child victims. Results. Because in reality there are still many cases of violence and sexual abuse against children. Case No. 3 Pid.Sus-Anak/2023/PN Mll was a case of maltreatment in which the public prosecutor charged the defendant with Article 170 paragraph (2) to 1 of the Criminal Code Jo. Article 81 of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System which basically states that juvenile offenders must be detained in a Special Correctional Institution for Children. Conclusion. Through this paper, it is hoped that law enforcement officials will synergize in implementing child protection and children's rights, especially regarding the guarantee of child protection from violence and harassment.